To What Extent the Emergency Physicians in Riyadh City Are Aware of Patient Radiation Exposure From Diagnostic Imaging Requested in the Emergency Department - Alhawas, Abdulrahman Y (Cureus, 2020)
Introduction Radiological imaging that uses ionizing radiation in emergency departments (EDs) has increased with advances in radiological diagnostic methods. Emergency (ER) physicians’ awareness of the radiation doses and the associated cancer risks that the patients are exposed to was surveyed using a questionnaire. Aims To assess the ER physicians’ awareness of radiation doses associated with the diagnostic imaging and to describe their practice about discussing radiation risk with patients at different hospitals in Riyadh city, Saudi Arabia. Methods A prospective, questionnaire-based observational study was conducted in 2016 among 176 ER physicians at different hospitals in Riyadh city. The percentage knowledge score and the frequency of discussing radiation risk with patients based on responses to three scenarios were rated on a visual analog scale (VAS), where a score of 100 indicated that physicians would always discuss it. Results The overall mean knowledge score was 28% (95% CI: 22-34). None of the studied parameters (gender, experience, country of medical qualification, type of degree, and employment level) showed a significant correlation with the overall awareness of ED physicians about radiation exposure. Over three-quarters of physicians (77%) underestimated the lifetime risk of fatal cancer attributed to a single computed tomography (CT) scan of the abdomen. Majority of physicians (60%) reported never discussing radiation risk with patients. The frequency at which physicians were discussing radiation risk with patients varied greatly depending on the clinical scenario (mean VAS scores between 46 and 82). Conclusions ER physicians of different hospitals in Riyadh city had a varied knowledge about the radiation exposure risks, although overall the perception was inadequate. The physicians should receive education, and the diagnostic imaging request may need to include information on radiation doses and risks.